2022
DOI: 10.3390/biomedicines10030652
|View full text |Cite
|
Sign up to set email alerts
|

Hypouricemia and Urate Transporters

Abstract: Hypouricemia is recognized as a rare disorder, defined as a serum uric acid level of 2.0 mg/dL or less. Hypouricemia is divided into an overexcretion type and an underproduction type. The former typical disease is xanthinuria, and the latter is renal hypouricemia (RHUC). The frequency of nephrogenic hypouricemia due to a deficiency of URAT1 is high in Japan, accounting for most asymptomatic and persistent cases of hypouricemia. RHUC results in a high risk of exercise-induced acute kidney injury and urolithiasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 105 publications
0
27
0
Order By: Relevance
“…It exists in the blood and excreted with urine, and the kidney plays an important role in the regulation of uric acid level, the body, 60%~70% of uric acid excretion(18).Therefore, renal function impairment or purine metabolism disorders will cause changes in the body's uric acid levels (19). Uric acid has a variety of biological effects in the human body, which can promote the in ammatory response, and can also serve as an antioxidant and endogenous free radical scavenger, and is closely related to adult chronic obstructive pulmonary disease.In addition to chronic obstructive pulmonary disease, respiratory diseases are also closely associated with pulmonary interstitial brosis, asthma, obstructive sleep apnea and hypoventilation syndrome, lung cancer, and pneumonia.Meanwhile, it also participates in the occurrence and development of diabetes, liver system, kidney system, cardiovascular, cerebrovascular and other systemic diseases (20,21). The majority of patients in the intensive care unit usually experience a variety of pathogenic processes, such as ischemia-reperfusion injury, in ammation, and coagulopathy.Uric acid may be a factor involved in the aforementioned pathogenic processes, and may be of potential value for assessing changes in clinical conditions and disease outcomes.The results of this study suggest that a decreased serum uric acid level is a predictor of RMPP.…”
Section: Discussionmentioning
confidence: 99%
“…It exists in the blood and excreted with urine, and the kidney plays an important role in the regulation of uric acid level, the body, 60%~70% of uric acid excretion(18).Therefore, renal function impairment or purine metabolism disorders will cause changes in the body's uric acid levels (19). Uric acid has a variety of biological effects in the human body, which can promote the in ammatory response, and can also serve as an antioxidant and endogenous free radical scavenger, and is closely related to adult chronic obstructive pulmonary disease.In addition to chronic obstructive pulmonary disease, respiratory diseases are also closely associated with pulmonary interstitial brosis, asthma, obstructive sleep apnea and hypoventilation syndrome, lung cancer, and pneumonia.Meanwhile, it also participates in the occurrence and development of diabetes, liver system, kidney system, cardiovascular, cerebrovascular and other systemic diseases (20,21). The majority of patients in the intensive care unit usually experience a variety of pathogenic processes, such as ischemia-reperfusion injury, in ammation, and coagulopathy.Uric acid may be a factor involved in the aforementioned pathogenic processes, and may be of potential value for assessing changes in clinical conditions and disease outcomes.The results of this study suggest that a decreased serum uric acid level is a predictor of RMPP.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the cellular transport system of uric acid, it is known that in humans, almost all uric acid is filtered by the glomeruli and reabsorbed from the renal tubules through transporter subunits present on the surface of the glomerular lumen (URAT 1), before reaching the basolateral membrane where the URATv1 transporter is located, which plays an important role in uric acid absorption in endothelial cells [ 27 , 28 ]. Experimental studies have shown that uric acid transporters are also expressed in vascular endothelial cells, contributing to inflammation; oxidative stress; and, hence, endothelial dysfunction through a reduction in endothelial NO [ 29 , 30 ].…”
Section: Endothelial Dysfunction and Hyperuricemiamentioning
confidence: 99%
“…Considering the solubility of uric acid, hyperuricemia can be defined as a serum uric acid level > 7.0 mg/dL, regardless of sex [11]. Because the kidneys are the major route of uric acid excretion, a reduction in GFR may lead to hyperuricemia.…”
Section: Hyperuricemia and The Kidneysmentioning
confidence: 99%
“…Hyperuricemia is often associated with diabetes mellitus (DM) [11], and it seems that insulin resistance correlates with serum uric acid levels and inversely correlates with the renal clearance of uric acid [26]. In addition, hyperuricemia may be associated with an increased risk of DKD in patients with type 2 DM [27].…”
Section: Diabetic Kidney Disease (Dkd)mentioning
confidence: 99%
See 1 more Smart Citation